The first beginnings of science morphology and its overlap with science grammar - zeghbib, Ghania (Milev Journal of Research and Studies, 2021)
The aim throngh this research paper is to identify the rerhy beginnings of morphology and know the reasom of ist overlap with grammar, especially if we know that the ancient hterature and works comtaine morphology within the grammatical stidies as part of grammar which made the beginings of this science ; togther and no specific time was knownto it .we will tryin our research on the emergence of morphology and ist importance within arabic sciences in addition to the ovrlap of morphology and grammar among the ancients and contimation of this overlap among the modernists despite its imdepence